2010
DOI: 10.1002/app.31745
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to soluble polyaniline and its copolymers with toluidines

Abstract: Homopolymers of aniline, toluidines and their copolymers were synthesized by chemical oxidative polymerization using different ratios of monomers in the feed in H 2 SO 4 medium. The synthesized polymers were characterized by employing Fourier transform infrared, UV-visible, proton nuclear magnetic resonance, X-ray diffraction techniques for understanding the details of the structure of the synthesized polymers. Morphological, thermal, and electrical conductivity of the as synthesized polymers were also studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…A broad band at 2θ = 25.19 is due to the amorphous nature of the PMT chains. [47] Other six sharp peaks at 2θ = 27.78, 32.1, 46.1, 54.7, 57.38, and 76.78 could be assigned to the characteristic diffraction peaks of AgCl (111), (200), (220), (311), (222), and (420) facets, for the Ag-PMT nanocomposites and that are in good agreement with reported data (JCPDS no. 06-0480).…”
Section: Xrd Analysissupporting
confidence: 89%
“…A broad band at 2θ = 25.19 is due to the amorphous nature of the PMT chains. [47] Other six sharp peaks at 2θ = 27.78, 32.1, 46.1, 54.7, 57.38, and 76.78 could be assigned to the characteristic diffraction peaks of AgCl (111), (200), (220), (311), (222), and (420) facets, for the Ag-PMT nanocomposites and that are in good agreement with reported data (JCPDS no. 06-0480).…”
Section: Xrd Analysissupporting
confidence: 89%
“…The peaks observed at 500-600 cm -1 , 1067 cm -1 are due to the presence of clay in the co mposite. The peak assignments are listed in the table [22][23][24][25]. The spectrum showed characteristic peaks of polyaniline and clay at 1067 and 1430 cm -1 , the IR spectrum for the different co mposites is shown in the figure 1.…”
Section: Characterizati Onmentioning
confidence: 99%
“…J. Bae et al suggested that higher wt% of PSS decreases the crystallinity of the PANI particles [35]. As well as Swaruparani et al also suggested that introduction of methyl group on an aniline unit increases the intermolecular chain spacing and amorphousness as compared with the pure PANI [36]. The above results specify that introduction of higher wt% of PSS and methyl group of o-toludine are hindering the exhibition of typical PANI crystalline phase.…”
Section: Particle Size and Tem Of Water Dispersed Pat:pssmentioning
confidence: 49%